Optimization of speed response of super-high-speed electric air compressor for hydrogen fuel cell vehicle considering the transient current. (3rd August 2021) - Hu, Donghai; Yang, Lei; Yi, Fengyan; Hu, Leli; Yang, Qingqing; Zhou, Jiaming
Abstract: A super-high-speed electric air compressor for a hydrogen fuel cell vehicle must have a wide speed range and high-speed regulation response capacity. However, due to the distortion of the air gaps magnetic field of the super-high-speed permanent magnet synchronous motor (SHSPMSM) in the super-high-speed domain, the motor's output torque capacity is reduced. Then its speed regulation response capacity is weakened. To solve this problem, firstly, we analyze the effect of transient current on the speed regulation response of the super-high-speed PMSM. Secondly, we proposed a new speed regulation control method, the transient current injection (TCI) control method. Finally, simulation analysis and experimental results demonstrate the effectiveness of the proposed control method. Under target speed of 151, 703 rpm, the average electromagnetic torque of SHSPMSM using the TCI control method is increased by 3%. Furthermore, the speed regulation response time decreased by about 0.49s. Highlights: The voltage model of super-high-speed permanent magnet synchronous motor (SHSPMSM) considering transient current is established. A new speed control method, transient current injection (TCI) method, is proposed. The effectiveness of the proposed method is verified by simulation and experiment.